Material pre-straining effects on fracture toughness variation in offshore wind turbine foundations - Anandavijayan, Satya; Mehmanparast, Ali; Brennan, Feargal; Chahardehi, Amir (Elsevier, 2021)
S355 structural steel is a commonly used material in the fabrication of foundation structures of offshore wind turbines, which are predominantly supported using monopiles. During the manufacturing process of monopile foundations, S355 steel plates are pre-strained via a three point bending and rolling process, which subsequently changes the mechanical, fatigue and fracture properties of the material. The aim of this study is to investigate the variation in fracture toughness of S355 material by considering a range of pre-strain levels induced during the manufacturing process. Fracture toughness tests have been performed on compact tension specimens made of the as-received, 5% and 10% pre-strained S355 material. The test results have shown that the fracture toughness of the material decreases as the percentage of pre-straining increases. An empirical correlation has been derived between the yield strength of the material, the plastic pre-strain level and the fracture toughness values. The drawn relationship can potentially be utilised in the life assessment of offshore wind turbine monopile foundations to give a relatively accurate estimate of the remaining life by considering realistic values of fracture toughness post-fabrication, which results in better informed design and assessment.
Keywords: Manufacturing effects; Material pre-straining; Offshore wind; S355; Fracture toughness